Pyridoxine exerts antioxidant effects in cell model of Alzheimer’s disease via the Nrf-2/HO-1 pathway - Li, Chen; Wang, Ruili; Hu, Chunting; Wang, Hui; Ma, Qiaoya; Chen, Songsheng; He, Ya (Cellular and Molecular Biology, 2018)
Pyridoxine is a water- soluble pyridine derivative. The effect of pyridoxine in cell models of Alzheimer’s disease (AD), and the potential mechanisms involved, are not fully understood. In this study, the anti-AD effects of pyridoxine were studied in an AD cell model using a combination of techniques viz MTT assay, western blotting and assays for reactive oxygen species (ROS). Assays were also carried out to determine the mechanism underlying the antioxidant effects of pyridoxine. The results obtained revealed that pyridoxine exerted a protective potential against AD, attenuated ROS levels, decreased the expressions of cytoplasmic Nrf2, and upregulated whole-cell HO-1 expression. These results suggest that the anti-AD effect of pyridoxine may be attributed to its anti-oxidant property elicited via stimulation of the Nrf2/HO-1 pathway.